Cyclic Deformation and Microstructural Behavior of Reduced Activation Ferritic-Martensitic Steels - Batista, Maria Natalia (2014)
The present paper presents results about cyclic behaviour and the evolution of the dislocation structure of reduced activation ferritic–martensitic steels and commercial martensitic steels AISI 410 and 420. The variation of the free dislocation density within subgrains and subgrain size was mainly analysed during the cyclic softening of EUROFER 97 steel. From the analysis of the flow stress components, the friction and back stresses, and the information of the evolution of the dislocation structure, it could be concluded that the softening of tempered martensitic steels at 20°C is produced by the contribution of the friction stress and aided later by the back stress.